Pre-Scaling up of Animal Drawn Wheat Row Planter in Selected Districts of Arsi, West Arsi and Bale Zones (American Journal of Aquaculture and Animal Science, 2023)
Pre-scaling up of the animal-drawn wheat row planter was done in three specifically chosen districts: Tiyo from Arsi, Dodola from West Arsi, and Sinana from Bale zones. The goals were to increase wheat production and productivity using this technology, improve farmers’ knowledge and skills in using the improved technology, and build local capacity for future technology scaling up. Six peasant associations from these districts were specifically chosen based on their accessibility from a list of peasant associations. Then, in order to scale up the technology, a total of six groups, one at each peasant association, each with an average of fifteen farmers made up of men, women, and youth, were formed. A total of 69 participants from three districts, including 62.3% men and 37.7% women, took part in the theoretical and practical training. The major emphasis of the instruction was on how to use technology and its respective advantages. Additionally, training was given to competent microenterprises that might close the technological gap, and connections with other stakeholders were also made. The purpose of the mini-field day was to exchange knowledge and experiences, and all of the farmers who saw the demonstration recognized the benefits of this technology. Therefore, it is advised that the technique for animal-drawn wheat row planting be further promoted, made more widely known, and spread around the wheat-producing farm families around the study area and similar areas.